Assessment of core endurance and shoulder proprioception in dental students with and without forward head posture - Reem Sayed Dawood; Osama Ragaa Abdelraouf; Saif Mehmed; Ezzat ELSayed Moubarak; Amal A. Elborady (Bulletin of Faculty of Physical Therapy, 2023)
Abstract Background One of the most prevalent musculoskeletal issues in dentistry is forward head posture (FHP). Proprioception and core endurance are crucial for maintaining proper posture. Objective The aim of this study was to compare dental students with and without FHP in terms of their core endurance and shoulder proprioception. Methods Using kinovea software, a cross-sectional study was conducted on 30 dental students who had FHP with a craniovertebral angle less than 49 degrees. The control group consisted of 30 additional dental students without FHP. Trunk anterior flexor, posterior extensor, right and left flexors were tested using the McGill method to determine core endurance. The isokinetic Biodex system was used to measure shoulder proprioception. Results Independent t-test results revealed that core endurance was significantly lower in the group with forward head posture compared to the control group (p 0.05), while shoulder proprioception did not differ significantly between groups (p > 0.05). Conclusion In comparison to dental students without forward head posture, male dental students with FHP have normal shoulder joint proprioception and impaired core endurance holding time. This could be a risk factor for a variety of musculoskeletal issues in dentists.